Solar combined cycle with high-temperature thermochemical energy storage. (1st August 2021) - Ortiz, C.; Tejada, C.; Chacartegui, R.; Bravo, R.; Carro, A.; Valverde, J.M.; Valverde, J.
Highlights: The proposed SCC-TCES allows boost the solar share in combined cycles above 70%. Receiver thermal-to-electric efficiency are in the range 45–50%. Annual performance is evaluated through four solar radiation clusters from real data. A 360° heliostats solar field with three cavity receivers (200 m tower) is designed. Abstract: The present work proposes integrating a high-temperature thermochemical energy storage cycle to boost the solar contribution in solar combined cycles. The main feature of the plant is the possibility of storing solar energy at a very high temperature and releasing it on demand to drive the combined cycle in the absence of solar radiation. Based on the reversible calcination-carbonation of CaCO3 /CaO, the Calcium-looping process is proposed since it allows power production above 900 °C by using cheap, non-toxic and widely available raw materials (i.e. limestone or dolomite). Based on an air-open and a CO2 -closed combined cycle, two potential configurations are modelled and analysed, including designing a 360° solar field with a 200-meter tower. The novel solar combined cycle analyzed in the present work enhances the annual solar share above 50%, whilst the current state-of-the-art technology is below 15%. From actual solar irradiation data and clustering analysis, results show overall plant efficiencies over 45% (considering off-design performance) with a very high dispatchability, which justifies the interest in further developing this novel cycle.